Drivers of augmented reality shopping adoption for high-involvement products in South Africa - Kate M. Ngobeni; Khathutshelo M. Makhitha (South African Journal of Information Management)
Background: Online shopping has revolutionised the way we buy products, providing convenience and accessibility. However, one of the challenges of online shopping has been the inability to physically try products before making a purchase. This limitation led to the emergence of online augmented reality (AR) shopping, a technology-driven solution that has transformed the online retail experience, especially for expensive products that require extensive search. Despite the potential that AR technology has exhibited, the retail sector has not yet fully embraced it and research on its impact on consumer behaviour is still in its early stages.